Seed priming with melatonin alleviates cadmium and drought stress by regulating growth, physiological functions and defense mechanisms in tomato - Tayeb Muhammad; Tao Yang; Juan Wang; Baike Wang; Qinghui Yu (Plant Biosystems, 2026)

Genomic characterization, expression and functional analysis of the plant homeodomain (PHD) family in tomato (Solanum lycopersicum L.) under abiotic stresses - Tayeb Muhammad; Tao Yang; Haitao Yang; Laipeng Zhao; Xin Bai; Juan Wang; Baike Wang; Qinghui Yu (Planta, 2026)

Therapeutic intervention strategies for Nipah virus infection: a scoping review - Ikhwan Yuda Kusuma; Bizhar Ahmed Tayeb; Muhammad Jayyid Zidan; Septi Nurkhasanah; Rian Nurahman; Ilil Maidatuz Zulfa (Infectious Diseases, 2026)

Genome-wide identification of RCC1 gene family in pepper (Capsicum annuum L.) and functional analysis of CaRCC1-16 under heat stress - Nadia Sajjad; Tayeb Muhammad; Altaf Hussain; Yong Kang; Qiaomin Yang; Mahnoor Khattak; Minghui Lu (Plant Cell Reports, 2026)

Electrochemical detection of nitrite ions by solid-state synthesized Au2O3@NiO/ZnO nanocomposite for the environmental safety assessment - Mohammed Muzibur Rahman; Abdulkarim Albishri; Saeed D. Alahmari; Amjad E. Alsafrani; Nouf M. Alourfi; O. Madkhali; Roaa A. Tayeb; Muhammad Fazle Rabbee (Chemical Engineering Journal, 2026)

A novel F-box gene, SlSE2.2, is responsible for the stigma exsertion degree in tomato (Solanum lycopersicum) - Pan Zhao; Yanhong Zhang; Zhengliang Sun; Baohui Cheng; Liangzhe Meng; Tayeb Muhammad; Yuhe Yao; Muhammad Mehran Abbas; Xiangqiang Zhan; Fei Zhang; Yan Liang (Plant Science, 2025)

Multifunctional assessment of copper-doped ZnO nanoparticles synthesized via gliding arc discharge plasma technique: antioxidant, antibacterial, and photocatalytic performance - Latra Benkhira; Mohammed Fouad Ferhat; Mohammed Tayeb Oucif Khaled; Ridha Messai; Nourelhouda Bounedjar; Mohammed Laid Tedjani; Abdelhalim Zoukel; Muhammad Humayun; Mohamed Bououdina (Environmental Science and Pollution Research, 2024)

Improving Significant Wave Height Prediction Using a Neuro-Fuzzy Approach and Marine Predators Algorithm - Rana Muhammad Adnan Ikram; Xinyi Cao; Tayeb Sadeghifar; Alban Kuriqi; Ozgur Kisi; Shamsuddin Shahid (Journal of Marine Science and Engineering, 2023)
This study investigates the ability of a new hybrid neuro-fuzzy model by combining the neuro-fuzzy (ANFIS) approach with the marine predators’ algorithm (MPA) in predicting short-term (from 1 h ahead to 1 day ahead) significant wave heights. Data from two stations, Cairns and Palm Beach buoy, were used in assessing the considered methods. The ANFIS-MPA was compared with two other hybrid methods, ANFIS with genetic algorithm (ANFIS-GA) and ANFIS with particle swarm optimization (ANFIS-PSO), in predicting significant wave height for multiple lead times ranging from 1 h to 1 day. The multivariate adaptive regression spline was investigated in deciding the best input for prediction models. The ANFIS-MPA model generally offered better accuracy than the other hybrid models in predicting significant wave height in both stations. It improved the accuracy of ANFIS-PSO and ANFIS-GA by 8.3% and 11.2% in root mean square errors in predicting a 1 h lead time in the test period.

Short-term probabilistic prediction of significant wave height using bayesian model averaging: Case study of chabahar port, Iran - Rana Muhammad Adnan; Tayeb Sadeghifar; Meysam Alizamir; Masouad Torabi Azad; Oleg Makarynskyy; Ozgur Kisi; Reza Barati; Kaywan Othman Ahmed (Ocean Engineering, 2023)